Computational discovery of soybean promoter cis‐regulatory elements for the construction of soybean cyst nematode‐inducible synthetic promoters. Issue 8 (3rd June 2014) - Liu, Wusheng; Mazarei, Mitra; Peng, Yanhui; Fethe, Michael H.; Rudis, Mary R.; Lin, Jingyu; Millwood, Reginald J.; Arelli, Prakash R.; Stewart, Charles Neal
Summary Computational methods offer great hope but limited accuracy in the prediction of functional cis‐regulatory elements; improvements are needed to enable synthetic promoter design. We applied an ensemble strategy for de novo soybean cyst nematode (SCN)‐inducible motif discovery among promoters of 18 co‐expressed soybean genes that were selected from six reported microarray studies involving a compatible soybean–SCN interaction. A total of 116 overlapping motif regions (OMRs) were discovered bioinformatically that were identified by at least four out of seven bioinformatic tools. Using synthetic promoters, the inducibility of each OMR or motif itself was evaluated by co‐localization of gain of function of an orange fluorescent protein reporter and the presence of SCN in transgenic soybean hairy roots. Among 16 OMRs detected from two experimentally confirmed SCN‐inducible promoters, 11 OMRs (i.e. 68.75%) were experimentally confirmed to be SCN‐inducible, leading to the discovery of 23 core motifs of 5‐ to 7‐bp length, of which 14 are novel in plants. We found that a combination of the three best tools (i.e. SCOPE, W‐AlignACE and Weeder) could detect all 23 core motifs. Thus, this strategy is a high‐throughput approach for de novo motif discovery in soybean and offers great potential for novel motif discovery and synthetic promoter engineering for any plant and trait in crop biotechnology.